دراسة أسباب انفجار أنابيب مراجل محطة بانياس الكهروحرارية - داوود, صلاح (Latakia University Journal -Engineering Sciences Series, 2019)
يعرض هذا البحث دراسة عملية تم اجراؤها على بعض أنابيب المراجل البخارية العاملة في محطة توليد بانياس والتي تعرضت إلى انفجارات أدت الى توقفات فجائية في عملها، مما أدى الى خسائر مالية وفنية في المحطة . ركزت الدراسة على المواقع الأكثر تعرضاً لدرجات الحرارة المرتفعة ذلك لأن معظم الانفجارات قد حدثت في هذه المواقع . كما تم دراسة التأثيرالمشترك لكل من الإجهادات الحرارية والتآكلات الكيميائية على معدن أنابيب المراجل العاملة عند ضغوط ودرجات حرارة عالية . وتهدف الدراسة الى وضع المقترحات والحلول الكفيلة بتفادي تكرار انهيار الأنابيب وبالتالي تقليل التكاليف المتعلقة بذلك . ويمكن الأستفادة من نتائج هذا البحث في معرفة أسباب انفجار أنابيب المراجل البخارية في المحطات الكهروحرارية الأخرى العاملة في القطر العربي السوري . This research presents an applied study on some steam boiler tubes in power stations. These steam boiler tubes subject of study have really failed and caused immediate breakdowns in power stations. Such failures lead to a reduction in steam boiler tubes economical age, and an increase in financial and technical costs. Positions exposed to high temperature and pressure have been the focus of the study. In fact, the shared effect of temperature stress and chemical corrosion on boiler tubes metal has been also carefully studied. The purpose of the said study is to make propositions and put solutions that guarantee avoidance of repetitive failures and a reduction in money costs. Results of this empirical research can definitely help to solve the same problem in other power stations.